2020
DOI: 10.21203/rs.2.18445/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NTP42, a novel antagonist of the thromboxane receptor, attenuates experimentally induced pulmonary arterial hypertension

Abstract: Background NTP42 is a novel antagonist of the thromboxane prostanoid receptor (TP), currently in development for the treatment of pulmonary arterial hypertension (PAH). PAH is a devastating disease with multiple pathophysiological hallmarks including excessive pulmonary vasoconstriction, vascular remodelling, inflammation, fibrosis, in situ thrombosis and right ventricular hypertrophy. Signalling through the TP, thromboxane (TX) A 2 is a potent vasoconstrictor and mediator of platelet aggregation. It is also a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Several studies found that SQ30741, a TXA2‐PGH2 receptor antagonist, prevents and/or eliminates PH 53–56 . With regard to NTP42, a TX prostanoid receptor antagonist, a study demonstrated that it decreased PAH, including mPAP and right systolic ventricular pressure 57 . They concluded that NTP42 and TX prostanoid receptor antagonism contributes to eliminating PAH pathophysiology 57 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies found that SQ30741, a TXA2‐PGH2 receptor antagonist, prevents and/or eliminates PH 53–56 . With regard to NTP42, a TX prostanoid receptor antagonist, a study demonstrated that it decreased PAH, including mPAP and right systolic ventricular pressure 57 . They concluded that NTP42 and TX prostanoid receptor antagonism contributes to eliminating PAH pathophysiology 57 …”
Section: Resultsmentioning
confidence: 99%
“…[53][54][55][56] With regard to NTP42, a TX prostanoid receptor antagonist, a study demonstrated that it decreased PAH, including mPAP and right systolic ventricular pressure. 57 They concluded that NTP42 and TX prostanoid receptor antagonism contributes to eliminating PAH pathophysiology. 57 In addition, TX synthetase inhibitors, PGI2 analogs, PGI2 agonists, and TX inhibitors, help counteract the PH-inducing effects of TX.…”
Section: Cyclooxygenase (Cox) Thromboxane A2 and Prostacyclin Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…83 However, interest in thromboxane inhibition persists and a novel thromboxane receptor antagonist NTP42 has demonstrated promising results in preclinical studies. 84…”
Section: Anticoagulation Antiplatelets and Novel Therapeutics In Pahmentioning
confidence: 99%
“…83 However, interest in thromboxane inhibition persists and a novel thromboxane receptor antagonist NTP42 has demonstrated promising results in preclinical studies. 84 There is considerable interest in the exploration of additional therapeutic pathways in PAH, including therapies that might attenuate platelet and coagulation abnormalities. Elevated circulating serotonin in individuals with IPAH and APAH prompted considerable interest in serotonin as a potential therapeutic target.…”
Section: Additional Therapiesmentioning
confidence: 99%